Comparison of two chemotherapy regimens in patients with newly diagnosed Ewing sarcoma (EE2012): an open-label, randomised, phase 3 trial. Issue 10362 (29th October 2022) - Brennan, Bernadette; Kirton, Laura; Marec-Bérard, Perrine; Gaspar, Nathalie; Laurence, Valerie; Martín-Broto, Javier; Sastre, Ana; Gelderblom, Hans; Owens, Cormac; Fenwick, Nicola; Strauss, Sandra; Moroz, Veronica; et al.
Summary: Background: Internationally, a single standard chemotherapy treatment for Ewing sarcoma is not defined. Because different chemotherapy regimens were standard in Europe and the USA for newly diagnosed Ewing sarcoma, and in the absence of novel agents to investigate, we aimed to compare these two strategies. Methods: EURO EWING 2012 was a European investigator-initiated, open-label, randomised, controlled phase 3 trial done in 10 countries. We included patients aged 2–49 years, with any histologically and genetically confirmed Ewing sarcoma of bone or soft tissue, or Ewing-like sarcomas. The eligibility criteria originally excluded patients with extrapulmonary metastatic disease, but this was amended in the protocol (version 3.0) in September, 2016. Patients were randomly assigned (1:1) to either the European regimen of vincristine, ifosfamide, doxorubicin, and etoposide induction, and consolidation using vincristine, actinomycin D, with ifosfamide or cyclophosphamide, or busulfan and melphalan (group 1); or the US regimen of vincristine, doxorubicin, cyclophosphamide, ifosfamide, and etoposide induction, plus ifosfamide and etoposide, and consolidation using vincristine and cyclophosphamide, or vincristine, actinomycin D, and ifosfamide, with busulfan and melphalan (group 2). All drugs were administered intravenously. The primary outcome measure was event-free survival. We used a Bayesian approach for the design, analysis, and interpretation of the results. Patients who received at least one dose of study treatment were considered in the safety analysis. The trial was registered with EudraCT, 2012-002107-17, and ISRCTN, 54540667. Findings: Between March 21, 2014, and May 1, 2019, 640 patients were entered into EE2012, 320 (50%) randomly allocated to each group. Median follow-up of surviving patients was 47 months (range 0–84). Event-free survival at 3 years was 61% with group 1 and 67% with group 2 (adjusted hazard ratio [HR] 0·71 [95% credible interval 0·55–0·92 in favour of group 1). The probability that the true HR was less than 1·0 was greater than 0·99. Febrile neutropenia as a grade 3–5 treatment toxicity occurred in 234 (74%) patients in group 1 and in 183 (58%) patients in group 2. More patients in group 1 (n=205 [64%]) required at least one platelet transfusion compared with those in group 2 (n=138 [43%]). Conversely, more patients required blood transfusions in group 2 (n=286 [89%]) than in group 1 (n=277 [87%]). Interpretation: Dose-intensive chemotherapy with vincristine, doxorubicin, cyclophosphamide, ifosfamide, and etoposide is more effective, less toxic, and shorter in duration for all stages of newly diagnosed Ewing sarcoma than vincristine, ifosfamide, doxorubicin, and etoposide induction and should now be the standard of care for Ewing sarcoma. Funding: The European Union's Seventh Framework Programme for Research, Technological Development, and Demonstration; The National Coordinating Centre in France, Centre Léon Bérard; SFCE; Ligue contre le cancer; Cancer Research UK.